The creative function of water in the formation of the world around us - S. L. Shvartsev (Геодинамика и тектонофизика)
The article is focused on the evolution mechanism of the ‘inert’ and living world around us, which is determined by the creative function of water. Water and igneous rocks of basic and ultrabasic compositions create an abiogenic dissipative system that never reaches an equilibrium and therefore is capable of maintaining its continuous, strictly directed, geologically long-term development and the formation of numerous new minerals that are paragenetically associated with specific geochemical types of water. This system is equilibrium-nonequilibrium. It develops in a thermodynamic area, far from an equilibrium. It is non-linear, irreversible, and internally contradictory. In this system, water has the creative function: the hydrolysis mechanism continuously dissolves some minerals, with which the system is not in equilibrium, and, at the same time, creates others minerals, with which there is an equilibrium, including the mineral that have been absent on our planet. After the occurrence of photosynthesis, the system was supplemented with organic compounds and developed into the ‘water-rock-gas-organic matter’ system. The mechanisms of this system were generally described by V.I. Vernadsky, and we suggest to name this system after him. The Vernadsky system had not only repeatedly became more and more complicated, but acquired the capability of creating more complex organic compounds from simple carbohydrates, such as proteins, lipids, more complex carbohydrates, hemoglobin etc. With time, these components developed into living organisms. Regardless of the repeated complication of the system, the basic mechanisms of its evolution remain essentially the same, and water has preserved and enhanced its creative function through dissolving simple compounds and creating more complex ones. An important factor in the continuous complication of the system is the natural water cycle.